AB0541 Vertebral fracture assessment in osteoporotic ankylosing spondylitis patients. (23rd January 2014) - Cojocaru-Gofita, I.-R.; Cojocaru, I.; Musetescu, A.; Barbulescu, A.; Florea, M.; Rosu, A.; Ciurea, P.; Vreju, F.
Abstract : Background: Ankylosing Spondylitis (AS) is one of the most common chronic autoimmune and autoinflammatory diseases and it can be defined both by its debilitating phenotype and its major social impact. Bone mineral density is known to be decreased in patients with AS compared to non-diseased controls therefore quantifying the absolute risk of developing a vertebral fracture becomes esential in identifying the patient subset in whom the correct therapeutical measures are highly needed. Objectives: To study the incidence of vertebral fractures in osteoporotic patients with AS, and to educate health professionals who may be involved in the management of AS patients with possible spinal injuries, despite not being a rheumatologist Methods: We enroled 35 patients - all men- whom were admitted in our Clinical Department over a 2 year – period, between 2010 and 2012 and they all fulfilled the New York modified criteria for AS. In order to assess disease activity and severity we performed the following for the entire study group: Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), C-reactive protein (CRP) and erythrocyte sedimentation rate (ESR) and further more spinal mobility (Schober's test, chest expansion and occiput-to-wall distance), radiological damage (syndesmophytes, sacroiliitis grade) and Bath Ankylosing Spondylitis Function Index (BASFI). Bone mass density (BMD) of the lumbar spine was measured by dual energy X-ray absorptiometry (DXA) and all patients had a baseline thoracolumbar radiograph. A prevalent vertebral fracture was defined according to the Genant classification criteria. Results: Osteoporosis was identified in 20% patients and 28.57% of the patients had osteopenia. Vertebral fractures were identified in 14.28 % of the patients, and among them, 2 had at least 2 separate incidents- the majority of them were grade 2 (95% confindence intervals). In 57, 14% from the patients with osteoporosis we identified VF, but we found no reported VF in the ones with osteopenia. Logistic regression analysis showed that disease duration (OR per year 1.02, 95% CI 1.03-1.06, p = 0.011), Bath Ankylosing Spondylitis Functional Index score (OR per score 1.17, 95% CI 1.03-1.30, p = 0.015) and wall-occiput distance (OR per cm 1.15, 95% CI 1.08-1.23, p < 0.001) were all associated with prevalent fracture but there were no significant correlations of BMD with disease activity or severity variables (ESR, CRP and BASDAI all p< 0.01). Conclusions: AS is an independent factor for the development of osteoporosis induced vertebral fractures and the risk increases with the disease duration and the impairment of functional status. We also find it highly important that medical staff have an understanding of the extreme caution that is needed in the management of possible spinal injuries in patients with ankylosing spondylitis. Disclosure of Interest: None Declared